AI Strict Liability Vis-À-Vis AI Monopolization - Lior, Anat (Science and Technology Law Review, 2021)
Some argue that applying a strict liability regime on AI-inflicted damages may allow well-financed big AI companies to monopolize the industry. They hypothesize that a strict liability regime would expose AI companies to significant legal liability. Since small AI companies lack the necessary resources to pay for damages inflicted by their AI technology, a strict liability regime could erect barriers to entry for these small companies. Ultimately, the argument continues, such a regime would give a small group of companies a virtual monopoly on the AI industry. Thus, some conclude that strict liability inherently stifles innovation and should not be applied to emerging technologies, such as AI. This Article maintains that legislators should adopt a strict liability regime, and it rejects the above argument for two reasons. First, there is no substantial connection between a strict liability regime and the AI monopolization that is already underway. Second, insurance policies could mitigate the effects a strict liability regime may have on the capabilities of small AI companies to enter and compete in this important market. Therefore, the ongoing process of monopolization of the AI market should not by itself render strict liability a non-viable regime when AI-inflicted damages occur.